2009
DOI: 10.1007/s11738-009-0290-7
|View full text |Cite
|
Sign up to set email alerts
|

Rapid in vitro multiplication of Melia azedarach L. (a multipurpose woody tree)

Abstract: An efficient regeneration protocol for rapid multiplication of Melia azedarach, an economically as well as medicinally important timber-yielding tree, was developed. Nearly 90% of the culture exhibited axillary bud sprouting and multiple shoot formation from nodal segments derived from 20-year-old candidate plus tree on Murashige and Skoog (MS) medium supplemented with 5 lM 6-benzyladenine (BA). The highest shoot regeneration frequency (92%), maximum number of multiple shoots (19.7 ± 0.31) as well as shoot len… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(32 citation statements)
references
References 23 publications
4
27
0
1
Order By: Relevance
“…The addition of KCl and Ca(NO 3 ) 2 help in improving the growth of culture of woody legume. These findings are further supported by earlier reports (Rathore et al 2004;Husain and Anis 2009). According to Preece (1995), in vitro performance of explants can be improved by balancing the nutrient level in the medium.…”
Section: Effect Of Different Types Of Culture Mediasupporting
confidence: 92%
“…The addition of KCl and Ca(NO 3 ) 2 help in improving the growth of culture of woody legume. These findings are further supported by earlier reports (Rathore et al 2004;Husain and Anis 2009). According to Preece (1995), in vitro performance of explants can be improved by balancing the nutrient level in the medium.…”
Section: Effect Of Different Types Of Culture Mediasupporting
confidence: 92%
“…Means sharing the same letter are not significantly different (P = 0.05) using Duncan's multiple range test tried, BA was the most effective followed by Kn and 2 iP which is in accordance with earlier report on hybrid willow (S. matsudana 9 alba NZ-1002) by Bhojwani (1980). The effectiveness of BA on multiple shoot bud differentiation has also been demonstrated in a number of cases using a variety of explants Husain and Anis 2009;Siddique and Anis 2009). The differentiation of shoot buds was confirmed by histological examination of cultured explants.…”
Section: Effect Of Cytokininssupporting
confidence: 89%
“…It has been reported that ex vitro-rooted plants are better suited to tolerate environmental stresses (Phulwaria et al, 2011). Rooting under ex vitro conditions has been successfully utilized for the establishment of several woody plants including Tectona grandis (Tiwari et al, 2002), Vitex nigundo (Ahmad and Anis, 2007), Melia azedarach (Husain and Anis, 2009) and Tecomella undulata (Varshney and Anis, 2012). Therefore, auxin dipped ex-vitro rooting is the most effective method for root induction in the present investigation.…”
Section: Resultsmentioning
confidence: 74%